2020
DOI: 10.5620/eaht.e2020010
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive toxicity assessment of Olusosun municipal landfill leachate in Mus musculus using abnormal sperm morphology and dominant lethal mutation assays

Abstract: Mixture of xenobiotics in Olusosun landfill leachates (OSL) induced somatic and germ cell genotoxicity in eukaryotic cells. However, whether the DNA-damaged germ cells can increase reproductive failure, embryotoxicity and/or teratogenicity during fertilization remained unclear. The study herein investigated reproductive toxicity and embryotoxic effects of OSL in mice using abnormal sperm morphology and dominant lethal mutation assays. Six mice per group were exposed to 0.5 mL of 5, 10, 25, and 50% OSL (v/v, le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 44 publications
3
20
0
Order By: Relevance
“…The significant increase in MDA concentration in the testes of the rats suggests that the testes is a target of ALL induced toxicity, it is possible that some of the constituents of the leachate are testicular toxicants. This observation is similar to the findings of [ 46 ] who observed testicular and epididymal degeneration with significant decrease in sperm quality and quantity in rats exposed to Olusosun landfill leachate and [ 47 ] who also reported reproductive toxicities in male mice exposed to Olusosun landfill leachate. The observed increase in MDA concentration in the organs of the rats is consistent with the results of [ 48 ] in rats exposed to Eliozu land fill leachate in Port Harcourt.…”
Section: Resultssupporting
confidence: 91%
“…The significant increase in MDA concentration in the testes of the rats suggests that the testes is a target of ALL induced toxicity, it is possible that some of the constituents of the leachate are testicular toxicants. This observation is similar to the findings of [ 46 ] who observed testicular and epididymal degeneration with significant decrease in sperm quality and quantity in rats exposed to Olusosun landfill leachate and [ 47 ] who also reported reproductive toxicities in male mice exposed to Olusosun landfill leachate. The observed increase in MDA concentration in the organs of the rats is consistent with the results of [ 48 ] in rats exposed to Eliozu land fill leachate in Port Harcourt.…”
Section: Resultssupporting
confidence: 91%
“…At very close range to living organism, landfill leachate is very toxic [19]. Recent reports have shown that landfill leachate can instigate liver and kidney dysfunction, DNA, brain and importantly, testicular damages [1,19]. Moreover, organs constituting the male reproductive tract (especially the testis) function with regards to formation of gamete (sperm) [6,31] needed for fertilization of the female ova which as a result arise in progeny and continuity of life [6], and therefore of interest in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Wastes are unavoidably produced by anthropogenic activities, and poor waste management has recently resulted in serious public health and environmental contamination hazards [1]. These issues increase together with the steady increasing human population and industrial activities [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations